1983
DOI: 10.1063/1.94223
|View full text |Cite
|
Sign up to set email alerts
|

Water acoustic microscopy at suboptical wavelengths

Abstract: An acoustic microscope using water as the coupling medium has been operated at frequencies up to 4.4 GHz. The signal-to-noise ratio is sufficient for imaging and the acoustic images demonstrate that the resolution is better than 2000 Å when the instrument is operated in the nonlinear regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…3b. For a 4.4 GHz transducer, a resolution of 0.20 m was achieved beyond the theoretical limitation of 0.24 m by increasing the input power [163]. They found that some details in the specimen became visible during the increase of the input power level due to the nonlinear generation of higher harmonics, and the resolution could not be improved further after a certain level of input power was reached.…”
Section: Improvement Of Imaging Resolution Using Higher Harmonicsmentioning
confidence: 90%
See 1 more Smart Citation
“…3b. For a 4.4 GHz transducer, a resolution of 0.20 m was achieved beyond the theoretical limitation of 0.24 m by increasing the input power [163]. They found that some details in the specimen became visible during the increase of the input power level due to the nonlinear generation of higher harmonics, and the resolution could not be improved further after a certain level of input power was reached.…”
Section: Improvement Of Imaging Resolution Using Higher Harmonicsmentioning
confidence: 90%
“…Hadimioglu and Quate [163], and Rugar [148] looked at the problem from a slightly different standpoint. A single transducer and lens were used in their studies, and the acoustic microscope operated in the reflection mode as shown in Fig.…”
Section: Improvement Of Imaging Resolution Using Higher Harmonicsmentioning
confidence: 98%
“…This objective has generally been pursued with two approaches; one approach was to raise the acoustic frequency [2]. By means of this approach, Hadimiooglu and Quate achieved a resolution of 0.2 p by operating at about 4.4 GHz with the specimen in boiling water to minimize the attenuation of the coupling medium [3]. The second approach was to use low-velocity coupling media such as superfluid liquid helium [4].…”
Section: Introductionmentioning
confidence: 99%
“…This objective has generally been pursued with two approaches; one approach was to raise the acoustic frequency [2]. By means of this approach, Hadimiooglu and Quate achieved a resolution of 0.2 µ by operating at about 4.4 GHz with the specimen in boiling water to minimize the attenuation of the coupling medium [3]. The second approach was to use low-velocity coupling media such as superfluid liquid helium [4].…”
Section: Introductionmentioning
confidence: 99%